2008
DOI: 10.1099/mic.0.2007/012021-0
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature (23 °C) increases expression of biofilm-, cold-shock- and RpoS-dependent genes in Escherichia coli K-12

Abstract: Temperature serves as a cue to regulate gene expression in Escherichia coli and other bacteria. Using DNA microarrays, we identified 297 genes whose expression is increased at 23 6C compared to 37 6C in E. coli K-12. Of these genes, 122 are RpoS-controlled, confirming genome-wide the model that low temperature serves as a primary cue to trigger the general stress response. Several genes expressed at 23 6C overlap with the cold-shock response, suggesting that strategies used to adapt to sudden shifts in tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 67 publications
10
79
1
Order By: Relevance
“…In fact, the biofilm synthesis regulation is highly complex, but little information is available on different species. Biofilm producing ability and correlation of different attachment factors were evaluated in several bacterial strains such as pathogenic Staphylococcus aureus (25) and E. coli (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the biofilm synthesis regulation is highly complex, but little information is available on different species. Biofilm producing ability and correlation of different attachment factors were evaluated in several bacterial strains such as pathogenic Staphylococcus aureus (25) and E. coli (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In a study focusing on E. coli biofilm formation at low temperatures, 40 % of the genes preferentially expressed at 23 u C were shown to be controlled by RpoS (White-Ziegler et al, 2008). Of these genes, several are implicated in biofilm development and an RpoS mutation decreases biofilm formation at 23 u C (White-Ziegler et al, 2008).…”
Section: Adaptation Of Rna Metabolismmentioning
confidence: 99%
“…Consistent with this role, the Rcs phosphorelay has been shown to regulate the general stress response-associated sigma factor, s S , through the activation of RprA, a small non-coding RNA that positively controls the level of s S in the cell by base-pairing with the 59 end of the rpoS mRNA (Majdalani et al, 2001(Majdalani et al, , 2002. s S is involved in the adaptation of the bacteria to starvation, hyperosmotic shock, pH downshift and low temperature, and controls many genes during the transition from the exponential to the stationary phase of growth (Patten et al, 2004;Weber et al, 2005;White-Ziegler et al, 2008). Recent studies have reported that s S influences global gene expression and protein production within E. coli biofilms, suggesting that this alternative sigma factor may have an important function during biofilm formation (Collet et al, 2008;Ito et al, 2009).…”
Section: Introductionmentioning
confidence: 99%